2013
DOI: 10.1371/journal.pntd.0002049
|View full text |Cite
|
Sign up to set email alerts
|

Cholera Outbreaks in Nigeria Are Associated with Multidrug Resistant Atypical El Tor and Non-O1/Non-O139 Vibrio cholerae

Abstract: BackgroundThe current millennium has seen a steep rise in the number, size and case-fatalities of cholera outbreaks in many African countries. Over 40,000 cases of cholera were reported from Nigeria in 2010. Variants of Vibrio cholerae O1 El Tor biotype have emerged but very little is known about strains causing cholera outbreaks in West Africa, which is crucial for the implementation of interventions to control epidemic cholera.Methodology/Principal Findings V. cholerae isolates from outbreaks of acute watery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
96
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 49 publications
13
96
1
1
Order By: Relevance
“…Vibrio strains in this study were also considerably sensitive to nalidixic acid, ofloxacin, ciprofloxacin, chloramphenicol, and rifampicin (Table 2), contrary to the observation of Ottaviani et al [22], who reported resistance against rifampicin. Marin et al [16] also reported an intermediate/reduced sensitivity to chloramphenicol and ciprofloxacin, and resistance against nalidixic acid, contrary to the observation of this study. However, consistent with the observation of this study, Li et al [21] reported sensitivity of Vibrio strains isolated from cultured silver sea bream to rifampicin, while Opajobi et al [19] observed sensitivity of epidemic strains of V. cholerae to ofloxacin.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Vibrio strains in this study were also considerably sensitive to nalidixic acid, ofloxacin, ciprofloxacin, chloramphenicol, and rifampicin (Table 2), contrary to the observation of Ottaviani et al [22], who reported resistance against rifampicin. Marin et al [16] also reported an intermediate/reduced sensitivity to chloramphenicol and ciprofloxacin, and resistance against nalidixic acid, contrary to the observation of this study. However, consistent with the observation of this study, Li et al [21] reported sensitivity of Vibrio strains isolated from cultured silver sea bream to rifampicin, while Opajobi et al [19] observed sensitivity of epidemic strains of V. cholerae to ofloxacin.…”
Section: Discussioncontrasting
confidence: 99%
“…However, contrary to the report of Chiang and Chuang [20], V. vulnificus and V. cholerae in this study exhibited reduced sensitivity and resistance to ceftazidime (29%) and cefixime (17%), respectively ( Table 2). Li et al [21] reported remarkable sensitivity to the aminoglycosides (streptomycin and kanamycin), in agreement with the observation of this study; however, other reports [16,21] suggested otherwise. Vibrio strains in this study were also considerably sensitive to nalidixic acid, ofloxacin, ciprofloxacin, chloramphenicol, and rifampicin (Table 2), contrary to the observation of Ottaviani et al [22], who reported resistance against rifampicin.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although surveillance systems to monitor DR cholera are poor, resistance to first-line therapies such as tetracycline derivatives, ciprofloxacin, and chloramphenicol is prevalent in some geographical regions (12)(13)(14). Lower rates of resistance to azithromycin, potentially contributing to the drug's superior efficacy against cholera diarrhea in clinical trials, have been reported (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Vibrio cholerae is a human pathogen that causes a severe acute watery diarrhea called cholera, a waterborne disease characterized by severe dehydration 1,2 . Vibrio cholerae is a major public health problem because of its epidemic potential 3 .…”
Section: Introductionmentioning
confidence: 99%